FGF15/FGFR4 Integrates Growth Factor Signaling with Hepatic Bile Acid Metabolism and Insulin Action - Shin, Dong-Ju (American Society for Biochemistry and Molecular Biology, 2009)
The current studies show FGF15 signaling decreases hepatic forkhead transcription factor 1 (FoxO1) activity through phosphatidylinositol (PI) 3-kinase-dependent phosphorylation. The bile acid receptor FXR (farnesoid X receptor) activates expression of fibroblast growth factor (FGF) 15 in the intestine, which acts through hepatic FGFR4 to suppress cholesterol-7α hydroxylase (CYP7A1) and limit bile acid production. Because FoxO1 activity and CYP7A1 gene expression are both increased by fasting, we hypothesized CYP7A1 might be a FoxO1 target gene. Consistent with recently reported results, we show CYP7A1 is a direct target of FoxO1. Additionally, we show that the PI 3-kinase pathway is key for both the induction of CYP7A1 by fasting and the suppression by FGF15. FGFR4 is the major hepatic FGF receptor isoform and is responsible for the hepatic effects of FGF15. We also show that expression of FGFR4 in liver was decreased by fasting, increased by insulin, and reduced by streptozotocin-induced diabetes, implicating FGFR4 as a primary target of insulin regulation. Because insulin and FGF both target the PI 3-kinase pathway, these observations suggest FoxO1 is a key node in the convergence of FGF and insulin signaling pathways and functions as a key integrator for the regulation of glucose and bile acid metabolism.